A. Edlin: A Treatise on the Art of Bread-making - Davidson, Alan E (Petits Propos Culinaires, 1993)
A. Edlin: A Treatise on the Art of Bread-making: [London, printed for Vernor and Hood, Poultry, 1805], Blackawton, Tom Jaine, 1993: 110 pp, introduction by Tom Jaine, paperback, limited edition of 300 numbered copies, £7.50 (may be ordered post-free direct from Tom Jaine, Allaleigh House, Blackawton, Devon TQ9 7DL).